The use of plain abdominal x rays in the emergency department. Issue 3 (20th February 2009) - Smith, J E; Hall, E J
Abstract : Abdominal x rays expose patients to significant doses of radiation and have limited use in emergency medicine. This review explores the evidence supporting the use of abdominal x rays in the emergency department, with particular reference to recent guidelines published by the Royal College of Radiologists. The authors' recommendations for the use of abdominal x rays in the emergency department are given.